The spatial correlation of a Multiple-Input Multiple-Output and channel model using Huygens-Fresnel principle for underwater acoustic - Kiehbadroudinezhad, Shahideh (Array, 2019)
In this work, the spatial correlation of a multiple-input multiple-output (MIMO) for underwater acoustic (UWA) channel is modelled. To obtain the spatial correlation for such a channel, a mathematical method to model the effect of the surface on the acoustic propagation is studied. The sea surface has a significant impact on the underwater acoustic propagation (UWA) channel since the sound field is scattered, particularly in rough sea conditions. In a situation where the sea surface is calm, the reflection is specular. In contrast, a sea surface subject to high sea states generates scattered waves. In these conditions, more complex mathematical equations are required to model the propagation. Current analytical models have limitations in terms of complexity and are not practical. Therefore, this study aims to consider a specular reflection to model the time-varying sea surface on the UWA channel. It is a simple model with low computationally complexity and can be used to assess the performance of UWA communications. Specifically, the specular reflection and transmission of an acoustic wave at a calm sea surface is studied, using the Huygens-Fresnel principle and the superposition theorem. The analytical model is developed using physical oceanic parameters representing the sea conditions. The results show a good agreement with the experimental analysis.